Arithmetic learning modifies the functional connectivity of the fronto-parietal network. (February 2019) - Zhao, Hui; Li, Xiaoxi; Karolis, Vyacheslav; Feng, Yi; Niu, Haijing; Butterworth, Brian
Abstract: How Resting-State Functional Connectivity (RSFC) is modified by learning is an important but rarely asked question. Here we used functional near-infrared spectroscopy (fNIRS) to measure changes in RSFC after learning novel subtraction and multiplication facts by forty-one young adult volunteers. We also measured changes in regional hemoglobin concentration. Fronto-parietal RSFC was modified by arithmetic learning and the fronto-parietal RSFC configuration before learning predicted the effectiveness of arithmetic learning. We also found a significant learning effect indicated by a monotonic decrease in reaction time and an increase in accuracy. Regional task-dependent oxy-hemoglobin concentration differentiated subtraction from multiplication learning supporting previous fMRI findings. These results suggest the sensitivity and importance of fronto-parietal connectivity to arithmetic learning.